Race and ethnicity moderate the associations between lifetime psilocybin use and crime arrests - Jones, Grant; Al-Suwaidi, Maha; Castro-Ramirez, Franchesca; McGuire, Taylor C.; Mair, Patrick; Nock, Matthew K. (Frontiers in Psychiatry, 2023)
Psilocybin use has been linked to lowered odds of crime-related outcomes across a host of observational studies. No studies have investigated how these associations may differ among those of different races and ethnicities. Using a nationally-representative sample of 734,061 adults from the National Survey on Drug Use and Health (2002-2020), we investigated whether race and ethnicity moderate the associations between lifetime psilocybin use and four measures of crime arrests (property crime, assault, serious violence, and miscellaneous crimes). First, we replicated prior findings and demonstrated that psilocybin confers lowered odds of crime arrests for all four outcomes in question. Second, we demonstrated that race and ethnicity moderate the associations between lifetime psilocybin use and crime arrests for three of our four outcomes. Third, we examined the associations between psilocybin and crime arrests across different races and ethnicities (White, Black, Indigenous, Asian, Multiracial, and Hispanic participants). Psilocybin conferred lowered odds of at least one crime arrest outcome for all racial and ethnic groups except for Black and Hispanic participants. Future investigations should take an intersectional approach to studying the interrelationship of sociodemographic factors, psychedelic use, and crime, examine the structural factors (i.e., systemic racism) that may underlie these results, and investigate whether psychedelics can alleviate mental health disorders that contribute to cycles of recriminalization for communities of color.